The physical fitness profile of female students serves as a criterion for selecting participants in fitness aerobics - Levitskaya A.N.; Zheleznov N.N.; Ponomarev V.V. (Theory and Practice of Physical Culture, 2025)
Objective of the study was to validate and enhance the model parameters of physical fitness for female students who are candidates for sports classes in fitness aerobics at a technical university. Methods and structure of the study. The research was conducted at the Siberian Federal State University of Education from 2021 to 2024. The study involved 270 female students who participated in the university’s fitness aerobics sports program. Over the course of three years, the study was conducted in stages, focusing on the following aspects: physical development, physical fitness, and mobility of the musculoskeletal system. Results and conclusions. The analysis of the expert assessment revealed the key indicators of physical fitness for female students, including the long jump from a standing position, torso lifting in a minute, arm flexion and extension in a prone position in a minute, running distances of 100 meters and 2000 meters. Additionally, the assessment encompassed physical development parameters such as height, weight, chest circumference, hand dynamometry, and Vital capacity. The study also examined the mobility of the musculoskeletal system through exercises like bending forward from a seated position, performing the «bridge» exercise from a prone position, and demonstrating the transverse and longitudinal splits. The findings of this research underscore the significance of developing methodological frameworks for physical education that incorporate sport-based approaches, with a focus on identifying the structure of physical fitness and establishing model characteristics for its various components.